Atlas Escolar Costa Rica - Zamora, Andrea (My University, 2014)
Recurso multimedia para aprender sobre la geografía física y política de Costa Rica.

It is a multimedia resource that teaches about costarrican physical and social geograghy.
Keywords: multimedia; geografía; Costa Rica